The edges of the earth in ancient thought : geography, exploration, and fiction - Romm, James S. (Princeton University Press, 1992)
The "edges of the earth" became the basis of a literary tradition, surveyed here, revealing that the Greeks, and to a somewhat lesser extent the Romans, saw geography not as a branch of physical science but as an important literary genre.
Keywords: Classical literature -- History and criticism.; Geography in literature.; Littérature ancienne -- Histoire et critique.; Géographie dans la littérature.; BIOGRAPHY & AUTOBIOGRAPHY -- Literary.; HISTORY -- Ancient -- General.; Classical literature; Geography in literature; Antike; Exotismus; Literatur; Weltbild; Weltende -- Grenze; Klassieke oudheid.; Wereldbeeld.; Geografia (historia); Miscelanea grega (literatura); Miscelanea latina (literatura); Littérature antique -- Thèmes, motifs.; Géographie -- Dans la littérature.; Géographie -- Histoire.; Géographie antique.; Terre -- Dans la littérature.; Ideengeschichte Anfänge-500.; Geschichte 800 v. Chr.-200.; Classical literatures -- Special subjects -- Geography; Nonfiction; Criticism, interpretation, etc.